Control System Design : an introduction - Manke, B. S. (Mercury Learning and Information, 2018)
Covers the theory and mathematics needed to understand the concepts in control system design. The book explores the theory and mathematics needed to understand the concepts in control system design. It includes two US government articles on industrial control systems and the control system design for a solar energy storage system.